Peran Komite Sekolah Terhadap Pengawasan Dana Operasional Sekolah Di Mts DDI Mulamenre’e Kecamatan Ulaweng Kabupaten Bone - A. Syamsu Alam; Fajri Dwiyama; Nurlina Nurlina (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The objectives of this study are as follows: to find out the extent of the role of the school committee in supervising school operational funds in MTs DDI Mulamenre'e, to find out how the role of the school committee in MTs DDI Mulamenre'e and to find out the involvement of the role of the school committee in supervising school operational funds in MTs DDI Mulamenre'e. The results showed that 1) Based on the results of research and discussion, it can be understoodÂ that the role of the school committee MTs DDI Mulamenre'e starting from the role of the school committee as a consideration agency, supporting institution and as a controlling institution has been well implemented, seen by the school committee contributing direction, support or support and maintaining good relations with school residents with the support of direction given in the form of thought energy and Materials, as well as the provision of facilities and school committees are always present and involved in implementation activities. 2) supervision of operational funds of MTs DDI Mulamenre'e schools, namely setting implementation standards including the timing of implementation costs and determining implementation measurements which include measuring budget or fund efficiency and measuring the implementation of activities to determine positive impacts and negative impacts 3) The role of the school committee in supervising the operational funds of MTs DDI a schools because considering the funds from madrasah or schools are limited, so it becomes one.